SISTEM PAKAR DIAGNOSA KERUSAKAN HARDWARE KOMPUTER DENGAN METODE NAIVE BAYES BERBASIS WEBSITE - Ryan Rama Rottie; Bagas Setiyaki Wicaksono (CV. Multi Kreasi Media, 2024)
A computer is an electronic device that can receive and process data into information, run programs stored in memory, and can work automatically with certain rules. Lack of sufficient knowledge in dealing with problems with damage to computers makes people unable to identify the location of the damage that has occurred and how to deal with it. Therefore, an expert system is needed to help people find problems with damage to computers along with solutions and ways to handle them. That by using a web browser-based application to diagnose laptop damage using the Naïve Bayes method, it can facilitate the work of a technician, especially in terms of time efficiency when analyzing damage. expert systems can help users to analyze initial damage by using existing symptoms with a system that has been built with the Bayesian method having an accuracy rate of 100%.